The Distribution of Phytoplasmas in South and East Asia: An Emerging Threat to Grapevine Cultivation - Pierro, Roberto; Semeraro, Teodoro; Luvisi, Andrea; Garg, Harsh; Vergine, Marzia; De Bellis, Luigi; Gill, Harsimran K. (Frontiers in Plant Science, 2019)
Grapevine is largely cultivated in several parts of the world and a spurt in its cultivation has occurred in the last two decades in grapevine cultivated areas of South and East Asia, mainly in China, India, Japan, Korea, Thailand and Indonesia. Grapevine Yellows (GY) represent one of the most important diseases in viticultural areas of the world, and they have been assigned to five different groups: aster yellows [AY, (16SrI)], Peanut witches’ broom [PnWB, (16SrII)], X-disease (16SrIII), elm yellows [EY, (16SrV)] and Stolbur (16SrXII). This study provides a comprehensive overview of the presence of phytoplasma strains and their vectors associated with GY complex, and their potential impact on viticulture of the South and East Asia. In general, both AY and EY were reported on several herbaceous plants and/or cultivated plants in South and East Asia, along with its vector (Macrosteles fascifrons) that was largely reported in China and sporadically in Japan. Interestingly, AY and EY are yet not found in South and East Asia grapevine region, however its presence on difference plant species suggest the potential spread of the pathogen that may occur in grapevine region in near future. Additionally, a few reports also suggest the presence of Stolbur group in Asian countries, along with one study that found a Stolbur-related strain in China on Vitis vinifera. Similarly, PnWB was also frequently reported in India and China on several plant species, but not in grapes. Conversely, sporadic detections of phytoplasma strains related to X-disease in Thailand, South Korea and China, indicate that their potential influence in viticulture is rather negligible. Our review suggests that monitoring and control strategies against GY are essential in order to prevent epidemic phytoplasma spread, especially in vine devoted areas in Asia.